2023
DOI: 10.1039/d2gc04057c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of olefins by selective hydrodeoxygenation of lignocellulosic ketones

Abstract: The selective hydrodeoxygenation (HDO) of lignocellulose-derived ketones to olefins is a promising method for the upgrading of lignocellulosic biomass-derived molecules. Herein, zinc molybdate (ZnMoO4-E) with disordered layered stacking structure was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…8, the coexistence of Mo 6+ , Mo 5+ and Mo 6+ is evidenced by the Mo 3d XPS spectra of reduced MoO 3 , MoO 3 /CoO and CoMoO 4 catalysts. According to the literature, 4,29 the peaks at about 232.1 eV and 235.3 eV can be assigned to Mo 6+ species, the peaks at 230.4 eV and 233.6 eV can be attributed to Mo 5+ species, and the peaks at about 229.5 eV and 232.8 eV can be assigned to the Mo 4+ species. The O 1s XPS spectra of reduced MoO 3 , MoO 3 /CoO and CoMoO 4 catalysts have two peaks at about 531.4 eV and 530.5 eV.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…8, the coexistence of Mo 6+ , Mo 5+ and Mo 6+ is evidenced by the Mo 3d XPS spectra of reduced MoO 3 , MoO 3 /CoO and CoMoO 4 catalysts. According to the literature, 4,29 the peaks at about 232.1 eV and 235.3 eV can be assigned to Mo 6+ species, the peaks at 230.4 eV and 233.6 eV can be attributed to Mo 5+ species, and the peaks at about 229.5 eV and 232.8 eV can be assigned to the Mo 4+ species. The O 1s XPS spectra of reduced MoO 3 , MoO 3 /CoO and CoMoO 4 catalysts have two peaks at about 531.4 eV and 530.5 eV.…”
Section: Resultsmentioning
confidence: 92%
“…Based on the results of XPS and UV-Vis spectra, the reduced CoMoO 4 catalyst has higher oxygen vacancy concentration than the reduced MoO 3 and MoO 3 /CoO catalysts. In some previous literature, 4,30,36 it has been suggested that the oxygen vacancies generated by partially reduced metal oxide catalysts can serve as Lewis acid sites. This may be the reason why the reduced CoMoO 4 catalyst has higher concentration of acid sites.…”
Section: Activity Testmentioning
confidence: 99%
See 2 more Smart Citations
“…13 More recently, our group reported a much milder strategy (140 °C, 1 bar) for furan cycloaddition to produce PX via a different decarboxylation pathway (Scheme 1b) upon a POM@MIL-100(Fe) catalyst (POMs: polyoxometalates). 14 In that reaction, decarboxylation of AA, via a single electron transfer (SET) process induced by ligand-to-metal charge transfer (LMCT) between Fe(III)-carboxylates, preferentially occurred at 140 °C, thus avoiding formation of the 2,5-dimethylbenzoic acid intermediate. However, ∼14% of p-tolyl-2,5-xylylmethane (PTX) was formed in the products due to the high temperature and long reaction time (24 h).…”
Section: Introductionmentioning
confidence: 99%